Benzbromarone Analog SAR: Potent hURAT1 (SLC22A12) Inhibitors and Drug Transporter Interaction Studies - Jutabha P; Kumar V; Anzai N; Rice PJ; Lightner JW; Endou H; Wempe MF (Drug Design, Development and Therapy)
Promsuk Jutabha,1,2 Vijay Kumar,3 Naohiko Anzai,2,4 Peter J Rice,5,6 Janet W Lightner,6 Hitoshi Endou,7 Michael F Wempe3,8,9 1Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakarn, 10540, Thailand; 2Department of Pharmacology and Toxicology, Dokkyo Medical University School of Medicine, Tochigi, 321-0293, Japan; 3Department of Sciences, School of Pharmacy, University of Colorado Denver Anschutz Medical Campus, Aurora, CO, 80045, USA; 4Department of Pharmacology, Chiba University Graduate School of Medicine, Chiba, 260-8670, Japan; 5Department of Clinical Pharmacy, School of Pharmacy, University of Colorado Anschutz Medical Campus, Aurora, CO, 80045, USA; 6Department of Pharmacology, East Tennessee State University, Johnson City, TN, 37614, USA; 7Department of Pharmacology and Toxicology, Kyorin University School of Medicine, Mitaka, 181-8611, Japan; 8Department of Biological and Physical Sciences, Kentucky State University, Frankfort, KY, 40601, USA; 9University of Colorado Cancer Center, University of Colorado Denver, Aurora, CO, 80045, USACorrespondence: Michael F Wempe, Kentucky State University, 400 East Main St, Frankfort, KY, 40601, USA, Email Michael.Wempe@kysu.eduPurpose: There were two main purposes for this study. One, to report two benzbromarone analogs and test their in vitro activity in the URAT1 inhibition assay; and two, to probe the structure–activity relationship (SAR) of various benzbromarone analogs regarding other drug transporters that may play a role in the uric acid uptake/elimination interplay.Methods: In brief, chemical synthesis of two benzbromarone analogs was prepared using methods analogous to those reported. Furthermore, drug transporter protein inhibition was investigated in vitro using oocytes expressing hURAT1, hURATv1 (GLUT9), hOAT1, hOAT3, hOAT10, hNPT4, OATP1B1, OATP1B3 and OATP2B1 prepared and utilized to conduct inhibition studies. In addition, one novel benzbromarone analog was studied via in vivo rat pharmacokinetic experiments to determine apparent oral bioavailability.Results: Two analogs, 6-fluoro-benzbromarone ( 5) and 5,6-difluoro-benzbromarone ( 9), were synthetically prepared and 5 had a hURAT1 IC50 inhibition of 18 ± 4 nM, while analog ( 9) had an IC50 of 245 ± 64 nM. Analog ( 5) had good oral bioavailability (Fa) > 0.6 in rat. Eadie-Hofstee plot and double-reciprocal plot of the Michaelis–Menten equation are summarized for benzbromarone ( 2) and its major Phase I metabolite 6-hydroxy-benzbromarone ( 3).Conclusion: These results illustrate that the Km for [14C]UA uptake was not altered in the presence of 2 or 3, but rather the Vmax was reduced in the presence of inhibitors when added to the uptake solutions. As a result, these data support the notion that 2 and 3 inhibit [14C]UA uptake by non-competitive inhibition and not at the URAT1 binding site.Keywords: oocyte transporter system, Eadie-Hofstee plot, rat pharmacokinetics, organic anion drug transporters